Economic evaluation of cognitive behavioral therapy and Internet-based guided self-help for binge-eating disorder - Koenig, Hans-Helmut; Bleibler, Florian; Friederich, Hans-Christoph; Herpertz, Stephan; Lam, Tony; Mayr, Andreas; Schmidt, Frauke; Svaldi, Jennifer; Zipfel, Stephan; Brettschneider, Christian; Hilbert, Anja; De Zwaan, Martina; et al. (International Journal of Eating Disorders, 2018)
OBJECTIVE: To determine the cost-effectiveness of individual face-to-face cognitive behavioral therapy (CBT) compared to therapist guided Internet-based self-help (GSH-I) in overweight or obese adults with binge-eating disorder (BED). METHOD: Analysis was conducted alongside the multicenter randomized controlled INTERBED trial. CBT (n = 76) consisted of up to 20 individual therapy sessions over 4 months. GSH-I (n = 71) consisted of 11 modules combining behavioral interventions, exercises including a self-monitoring food diary, psychoeducation, and 2 face-to-face coaching sessions over 4 months. Assessments at baseline, after 4 months (post-treatment), as well as 6 and 18 months after the end of treatment included health care utilization and sick leave days to calculate direct and indirect costs. Binge-free days (BFD) were calculated as effect measure based on the German version of the Eating Disorder Examination. The incremental cost-effectiveness ratio (ICER) was determined, and net benefit regressions, adjusted for comorbidities and baseline differences, were used to derive cost-effectiveness acceptability curves. RESULTS: After controlling for baseline differences, CBT was associated with non-significantly more costs (+€2,539) and BFDs (+40.1) compared with GSH-I during the 22-month observation period, resulting in an adjusted ICER of €63 per additional BFD. CBTs probability of being cost-effective increased above 80% only if societal willingness to pay (WTP) was ≥€250 per BFD. DISCUSSION: We did not find clear evidence for one of the treatments being more cost-effective. CBT tends to be more effective but also more costly. If the societal WTP for an additional BFD is low, then our results suggest that GSH-I should rather be adopted.
EVALuna2:35689